The role of forgiveness towards happiness: Perceived social support as a mediator - Wijaya, Dzikria Afifah Primala; Qonita; Utami, Mellyna Putri (Insight: Jurnal Ilmiah Psikologi, 2023)
Dating represents a form of human relationship, ideally, based on love. Unfortunately, some dating relationships deviate from this ideal, leading to psychological violence experienced by one of the parties involved.. The purpose of this research is to find out how significant forgiveness contributes to the happiness of individuals who experience psychological violence in dating, by involving 101 respondents who are in the emerging aged stage who experience violence in lawyers. Three scales were involved: the HFS (Heartland Forgiveness Scale), the Oxford Happiness Scale, and The Multidimensional Scale of Perceived Social Support (MSPSS). This research used quantitative research methods with mediator analysis techniques using JAMOVI. Based on the results of this analysis technique, it indicates that social support functions as a mediator, contributing to 25.2% of the role of forgiveness in fostering happiness. Keyword: Dating emerging, adulthood, jamovi, psychological violence, quantitative